Experimental Study on RC Deep Beams with Non-Prestressed Tendons as Main Reinforcement - Seyed Mohammad Reza Mortazavi; Milad Shakiba (Journal of Rehabilitation in Civil Engineering)
In the present study, The main purpose is to focus on the applicability of using non-prestressed tendons as the main reinforcement in concrete beams. Therefore, the main reason for the analytical study is to develop a model that can predict the flexural behavior of RC beams with ordinary reinforcements and/or with non-prestressed tendons (cables). An experimental program, as well as a computational program, was designed to see the behavior of such concrete reinforced beams. To do so, 9 beam models of one concrete mix were cast. The beams were cast in accordance with ACI recommendations and all tests were conducted under the same condition. The beams tested include two types of beams with ordinary steel rebar and with cables (tendons). The beams studied in this research are classified as deep beams (L/h<4); so the effect of shear deformations was considered. In addition, test results were compared with the predicted theoretical values. The theoretical model was able to predict the experimental load-deflection curves almost accurately. Therefore, it was demonstrated that the same concepts of the normal reinforced concrete beams can be applied for reinforced concrete beams using tendons as main reinforcement for both stiffness and strength calculations. Also, the same methodology used in concrete beams with steel rebar is applicable to the ones with non-prestressed tendons. The results showed that using the nominal flexural strength equations of regular reinforced concrete beams can accurately predict the strength of the beams with cables.